The Phantom of the Matrix: Populärkulturella skämt och intertextuell kompetens på Internet - Jansson, Hanna (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2006)
In this article I discuss humouros and intertextual elements from the Internet fan site The Phantom of the Opera Discussion Board. By applying folkloristic tools of analysis to the material it becomes clear that although the "phans" discuss modern popular culture on the Internet, the poplore they produce follow the same patterns as older folklore. The phans share a common world with highly specific internal codes and discourses. By repeatedly combining various adaptations of the Phantom of the Opera with other narratives and texts the phans produce a comic effect. Either elements from "outer" texts, such as the Wizard of Oz or the Matrix, are claimed and placed within a Phantom context, or the characters of the Phantom är themselves extracted from their plot and relocated into, for instance, ABBA’s well known songs.Without clear specifications of the sources, it is up to the reader to identify the references and by adding to the others’ jokes one can prove that one has indeed succeeded in doing this. I therefore argue that "phan humour" can be regarded as a highly creative way to prove one’s status as a "real" phan, as well as a result and display of a broad intertextual and cultural competence.